The Effect of Total Productive Maintenance and Reliability-Centered Maintenance on Operational Performance Through Overall Equipment Effectiveness of Power Plant at PT PLN Indonesia Power UBP PLTU Banten 1 Suralaya - Adi Guszahari; Uli Wildan Nuryanto; Yolla Sukma Handayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to improve the performance of maintenance management at PT PLN Indonesia Power Unit Bisnis Pembangkitan PLTU Banten 1 Suralaya by implementing Total Productive Maintenance (TPM), Reliability Centered Maintenance (RCM), and Overall Equipment Effectiveness to support the reliability and efficiency of power plant operations. The causal descriptive quantitative research method was conducted through a survey of 255 operations and maintenance division employees, using a questionnaire via Google Forms. The results showed a significant and positive effect of implementing these methods on improving operational performance, aligning with the need to increase electricity consumption for households and industry. The study was conducted for four months, from April to July 2024 at the PLTU Suralaya location, Cilegon.